Акустойонні та акустоелектронні технології - Мачулін, В.Ф.; Лепіх, Я.І.; Оліх, Я.М.; Романюк, Б.М. (№5, 2007)
The new approach to problem solution of semi-conductor material control within the frame of silicon technology of KMON-devices manufacturing is presented as well as to active acoustic-electron devices characteristic control problem and creation of new generation gauges based on these devices. The approach is to use ultrasonic treatment of semi-conduct plates during implantation (acousticion technologies) and to investigate physical phenomena that occur during acoustic waves spread in anisotropic piezoelectrics (acoustic-electron technologies). Ef fectiveness and universality of acoustic-ion and acousticelectron methods which priorities are proved by patents for invention can play an important role for instrument-making industry, information technologies, machine building, as well as become the basis of such advance scientific and engineering trends as thin film technology, nanoelectronics, functional microelectronics, optoelectronics.